Control of Dendritic Cell Function Within the Tumour Microenvironment - Gupta, Yukti Hari; Khanom, Abida; Acton, Sophie E. (Frontiers in Immunology, 2022)
The tumour microenvironment (TME) presents a major block to anti-tumour immune responses and to effective cancer immunotherapy. The inflammatory mediators such as cytokines, chemokines, growth factors and prostaglandins generated in the TME alter the phenotype and function of dendritic cells (DCs) that are critical for a successful adaptive immune response against the growing tumour. In this mini review we discuss how tumour cells and the surrounding stroma modulate DC maturation and trafficking to impact T cell priming. Fibroblastic stroma and the associated extracellular matrix around tumours can also provide physical restrictions to infiltrating DCs and other leukocytes. We explore interactions between the inflammatory TME and infiltrating immune cell function, exploring how TME affects the generation of T cell-driven anti-tumour immunity. We also discuss the open question of the relative importance of antigen-presentation within the TME versus tumour-draining lymph nodes. Research to address these questions can provide insights to potentially increase immune surveillance and enhance anti-tumour immunity.